2010
DOI: 10.1111/j.1365-2052.2009.01964.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of extracellular matrix and prolactin on global gene expression profiles of primary bovine mammary epithelial cellsin vitro

Abstract: An in vitro bovine mammosphere model was characterized for use in lactational biology studies using a functional genomics approach. Primary bovine mammary epithelial cells cultured on a basement membrane, Matrigel, formed three-dimensional alveoli-like structures or mammospheres. Gene expression profiling during mammosphere formation by high-density microarray analysis indicated that mammospheres underwent similar molecular and cellular processes to developing alveoli in the mammary gland. Gene expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
1
20
1
Order By: Relevance
“…4a). Our observations are consistent with the results of other groups working on the 3D culture system of MECs, which showed that the initiation of alveoli-like morphology formation was primarily driven by the ECM, and the acinar structures were formed even in the absence of PRL (Naylor et al 2003, Riley et al 2010). However, Riley and coworkers (2010) have noted in their microarray study of the transcriptional profile of primary bovine MECs cultured on Matrigel, that PRL is necessary for the high expression levels of milk protein genes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…4a). Our observations are consistent with the results of other groups working on the 3D culture system of MECs, which showed that the initiation of alveoli-like morphology formation was primarily driven by the ECM, and the acinar structures were formed even in the absence of PRL (Naylor et al 2003, Riley et al 2010). However, Riley and coworkers (2010) have noted in their microarray study of the transcriptional profile of primary bovine MECs cultured on Matrigel, that PRL is necessary for the high expression levels of milk protein genes.…”
Section: Discussionsupporting
confidence: 82%
“…The most commonly used ECM derivative in this culture system is the reconstituted basement membrane (rBM) derived from the Engelbreth--Holm-Swarm (EHS) mouse sarcoma, commercially available as Matrigel TM . Although many interesting studies with the use of 3D MEC culture have been published, very few describe the regulation of bovine MEC differentiation in the context of their interaction with ECM components (Delabarre et al 1997, Kozłowski et al 2009, Riley et al 2010). The present study shows the rate and mechanisms of the proper development of acinar structures (mammospheres) formed by the bovine mammary epithelial cell line BME-UV1 cultured on Matrigel.…”
Section: Introductionmentioning
confidence: 99%
“…Also in primary bovine MEC cultures, PRL has been shown to upregulate the mRNA levels of several caseins (Choi et al, 1988). A high number of other genes are under the control of PRL stimulation, as has been shown in bovine MEC using microarray analyses (Stiening et al, 2008;Riley et al, 2010). In association with its role in MEC differentiation, PRL is also known to promote DNA synthesis and cell proliferation, as has been demonstrated in rabbit and bovine MEC (Suard et al, 1983;Olazabal et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…The use of large transcriptomic analysis (i.e., microarray or RNA sequencing) by which to study the adaptation of mammary gland to lactation and/or change in milk production under specific conditions has been carried out in mouse (4,54,122,123,143,189,191,217,236,256), rat (3,47,187), bovine (31,36,56,75,96,144,183,209,218,233,239), sheep (209), goat (71,163,164), human (121,139,147), pig (204), kangaroo (120), and seal (144). It is beyond the scope of the current review to present a thorough discussion of the results from those studies.…”
mentioning
confidence: 99%